Inverse Vaccination for Autoimmune Diseases: Insights into the Role of B Lymphocytes - Moncef Zouali (Cells)
A novel therapeutic approach, inverse vaccination, is being developed to combat autoimmune diseases and other inflammatory conditions. It aims to educate the immune system to recognize self-components as innocuous and stop reacting against them. Inverse vaccination, also referred to as tolerogenic vaccination, introduces autoantigens into the immune system to induce immune tolerance to the nominal antigen. In contrast to conventional vaccination, which aims to train the immune system to identify a pathogen as a potential threat that needs to be eradicated, inverse vaccination is designed to educate the immune system to recognize that an antigen is harmless and, consequently, extinguish the inflammatory attack of the tissues that contain the autoantigen. This article discusses recent progress in using inverse vaccination to design therapeutic interventions in several autoimmune diseases by deprivation of co-stimulatory signaling, tagging autoantigens to trigger immune tolerance in the liver, and mRNA vaccination. Also discussed is a tolerogenic feedback loop implicating B lymphocytes in inverse vaccination.